Alla scoperta dell’altro - Amalfitano, Elisabetta (Il sogno della farfalla, 2018)
Through a philosophical and historical excursus, the article highlights the most relevant stages when Western rationality tackled what was not considered to be rational (feelings, passion, strangers, women, slaves, children, artists etc.). Unlike what is commonly thought, Western Logos was far from being a welcoming, democratic or global system of thought and, from its onset, it excluded all those who would not conform to reason. For instance, the “great Greek democracy” promoted by Pericles was all but inclusive. Maximum achievement of rationality stands in an ideal of tolerance towards strangers and those who are different. Reason has never managed to understand in depth what is different, hence, it has marginalized it or even annulled it by considering it to be inferior, animal, or non-being. In order to eradicate the viruses of racism and xenophobia – which are now so threatening – it is therefore necessary to succeed in unmasking and reversing this Western logic that distances those who reject the Aristotelian model based on the principles of identity and non-contradiction, and which cannot admit that others can be equal to ourselves (as human beings) and, at the same time, different from ourselves (as endowed with their own specific identity).